Application of guided discovery learning model using a scientific approach to improve learning activities and outcomes - Muslimin (Journal of diversity in learning (JDIL), 2021)
From the results of the student evaluation, there were 8 students out of a total of 17 students or 47.1% of students who had not reached the Minimum Completeness Criteria (KKM), which was 70 with an average score of 69.7. The aims of this study were (1) to determine the application of the guided discovery learning model with a scientific approach to improve learning activities and outcomes; (2) To find out the increase in student activity and learning outcomes through guided discovery learning models with a scientific approach. This research uses two cycles of action research. Each cycle consists of four stages, namely: planning, implementation, observation, and reflection. The target of this research is the fifth grade students of SDN Wajik for the academic year 2019/2020. The data obtained in the form of formative test results, observation sheets of teaching and learning activities and interviews. The results of the research application of the guided discovery learning model using a scientific approach have a positive effect on increasing learning activities and outcomes, and this learning model can be used as an alternative in thematic learning.